Dynamical Computations of the FitzHugh- Nagumo Equation - Okey Oseloka Onyejekwe (Archive of Biomedical Science and Engineering - Peertechz Publications, 2021)
The Hodgin-Huxley model is one of the most widely studied biological systems of nonlinear differential equations that is applied to explore nerve cells activities via electrical communications. In this paper we consider some numerical aspects of a simplified version of this model known as the FitzHugh-Nagumo (FHN) equation. Dynamical experiments conducted herein not only confirm those obtained from earlier studies but also facilitate a better understanding of the qualitative features of the FHN model especially those that initiate the behavior a threshold-triggered excitation media. To this end, methods of dynamical system analysis such as bifurcation and linear stability analysis are deployed to investigate the general qualitative features of an inhibitor-activator system which characterizes the FHN system of equations.